Public health nursing : a textbook for health visitors, school nurses and occupational health nurses - Thornbory, Greta (Wiley-Blackwell, 2009)
This textbook explores the background to modern public health and public health nursing based on international and national guidelines. It looks at public health nursing, health visiting, the role of the school nurse and how they meet the public health agenda and the role of the occupational health nurse as a public health practitioner.